2014
DOI: 10.3389/fpls.2014.00117
|View full text |Cite
|
Sign up to set email alerts
|

Ovule development, a new model for lateral organ formation

Abstract: In spermatophytes the ovules upon fertilization give rise to the seeds. It is essential to understand the mechanisms that control ovule number and development as they ultimately determine the final number of seeds and, thereby, the yield in crop plants. In Arabidopsis thaliana, ovules arise laterally from a meristematic tissue within the carpel referred to as placenta. For a correct determination of the number of ovules, a precise establishment of the positions where ovule primordia emerge is needed, and a tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 78 publications
(138 reference statements)
1
107
0
1
Order By: Relevance
“…The miR159 family is highly conserved in land plants (Cuperus et al, 2011). Arabidopsis thaliana has three miR159 precursors, each of which generates a distinct mature sequence (miR159a, -b and -c; Jones-Rhoades et al, 2006).…”
Section: Overexpression Of Slmir159 Alters Ovule Development and Indumentioning
confidence: 99%
“…The miR159 family is highly conserved in land plants (Cuperus et al, 2011). Arabidopsis thaliana has three miR159 precursors, each of which generates a distinct mature sequence (miR159a, -b and -c; Jones-Rhoades et al, 2006).…”
Section: Overexpression Of Slmir159 Alters Ovule Development and Indumentioning
confidence: 99%
“…While the different tissues constituting the ovule and the genes involved in their development are well described, the first step of ovule primordia initiation and how these primordia arise from the placenta in a such regularly spaced pattern remains more elusive (reviewed in Cucinotta et al, 2014). So far, few genes have been involved in ovule initiation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between the primordial and boundary regions, as well as cytokinin regulation are required for the proper expression and localization of the PIN-FORMED1 (PIN1) auxin transporter and thus for proper auxin fluxes. Brassinosteroid signaling is proposed to support ovule initiation through the stimulation of ANT activity in ovule primordia (Huang et al, 2013;Cucinotta et al, 2014).…”
Section: Carpel Margin Meristems (Cmms) and Shoot Apical Meristem (Samentioning
confidence: 99%
“…Their work suggested that proper termination of the floral meristem may be required for the complete development of the CMM and ovules. Cucinotta et al (2014) reviewed the early ovule development with a focus on the formation of the CMM and the initiation of ovule primordia in Arabidopsis. They presented a model of ovule initiation that relates the functions of CUC and ANT genes as well as the action of auxin, cytokinin, and brassinosteroid hormones (Galbiati et al, 2013;Cucinotta et al, 2014).…”
Section: Carpel Margin Meristems (Cmms) and Shoot Apical Meristem (Samentioning
confidence: 99%
See 1 more Smart Citation